P6.074 Tailoring Clinical Knowledge Products For Guidance on Addressing Sexually Transmitted Infections and Blood-Borne Infection (STBBIs) to Meet the Different Needs of Family Medicine Practitioners in Canada. (13th July 2013) - Seto, J; Kapral, O; Wong, T; Gale-Rowe, M; Demers, A; Dodds, J; Fisher, W; Read, R; Steben, M
Abstract : Background: Moving clinical guidelines into practise requires the development of clinical knowledge products to aid family practitioners. A variety of product types and formats may need to be used to suit different needs by career-stage. Methods: To evaluate the sexually transmitted and blood-borne infections (STBBI) knowledge product needs of practitioners, information was elicited from a convenience sample (N = 207) of family medicine practitioners at a national Canadian family medicine forum in Toronto between November 15 and 17, 2013. Analysis was stratified by years of practise to identify ways to reach different generations of practitioners concerning STI and HIV clinical recommendations. The Fishers exact and chi-square test was used to determine statistical significance. Data was collected on preferences on clinical aids; methods used to update clinical knowledge; and preferred formats of accessing STI guidelines. Results: All practitioners expressed preferences for concise clinical aids such as algorithms (64.2%) and abbreviated pocket guides (35.3%), in addition to prompts on electronic medical records (32.9%). On-line training and education were preferred by early-career practitioners (< 5-yrs: 53.3%), compared to their mid-to-late career (≥ 5yrs) counterparts (26.1%; p = 0.004). More mid-to-late-career practitioners preferred classroom style workshops (73.9%) than their early-career counterparts (46.7%; p = 0.004). There were differences (p = 0.04) by years of practise concerning guideline format preferences. Early-career practitioners preferred mobile applications (38.5%) compared to hard-copy materials (17.6%). Mid-to-late-career practitioners appeared to prefer hard-copy materials (31.2%) in addition to mobile applications (37.7%). Conclusions: These findings demonstrate generational differences in preferred formats and methods of accessing STI and HIV clinical information; public health programmes may wish to deliver information using different approaches to reach different practitioners.